An alcohol extract prepared from the male flower of Eucommia ulmoides Oliv. promotes synoviocyte apoptosis and ameliorates bone destruction in rheumatoid arthritis - Yan Zhang (BMC, 2021)
Abstract Background Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease dominated by synovial hyperplasia and bone destruction. The male flower of Eucommia ulmoides Oliv. (EF) has been shown to exert effects on the inflammation caused by RA. However, how EF affects synoviocyte apoptosis and bone destruction on RA have not been investigated thoroughly. The effects of EF on apoptosis of human fibroblast-like synoviocytes-rheumatoid arthritis (HFLS-RA) cells, osteoclast differentiation of RAW264.7 cells, and bone destruction in a collagen-induced arthritis (CIA) model in rats were explored. Methods First, the main components of EF were identified by high-performance liquid chromatography. In vitro, we investigated the anti-proliferative and pro-apoptotic effects of EF on HFLS-RA cells by immunofluorescence assays, flow cytometry, real-time reverse transcription-quantitative polymerase chain reaction (RT-qPCR), and western blotting; we also investigated how EF influenced the differentiation of RAW264.7 cells into osteoclasts. In vivo, we used a rat model of CIA to investigate the effects of EF on anti-arthritis activity, toe swelling, Arthritis Score, serum levels of metabolic bone factors, and pathologic conditions. Micro-computed tomography was used to scan ankle joints. mRNA and protein expression of factors related to the nuclear factor-kappa B (NF-κB) pathway were determined by RT-qPCR and western blotting, respectively. Results EF inhibited synoviocyte proliferation and promoted apoptosis in a dose-dependent manner. EF inhibited osteoclast differentiation by inhibiting activation of the NF-κB pathway. EF reduced articular inflammation in CIA rats, inhibited the expression of pro-angiogenic factors, and delayed the destruction of articular cartilage and bone. Our data indicated that EF acted via a mechanism related to bone metabolism induced by the NF-κB pathway. Conclusions EF exerts a potential therapeutic effect upon RA. Our research will help to elucidate the potential pharmacologic mechanisms associated with the beneficial effects of EF, and provide an experimental basis for EF application in clinical treatments. Graphical Abstract